Influência do desempenho acadêmico na percepção de justiça no ambiente de aprendizagem: um estudo com alunos do curso de Ciências Contábeis em universidades federais mineiras - Karla Luisa Costa e Costa (2017)
The present study had as general objective to look for evidences that allow to identify the relationship between the academic performance of graduation students in accounting sciences and their perception of justice, segregated in the dimensions of distributive, procedural and interactional justice. The theoretical constructs of the research were based on the works of Homans (1961), Adams (1965), Colquitt (2001), Chory-Assad (2007), Peter et al., 2012, Kovaevi et al. (2013) and Simil (2016). From these works, three research hypotheses were drawn: H1: Academic performance tends to influence the perception of distributive justice; H2: Academic performance tends to influence the perception of procedural justice; H3: Academic performance tends to influence the perception of interactional justice. The methodology consists of a qualitative and quantitative approach, which had as sample 534 graduate students of Accounting Sciences from nine federal universities in Minas Gerais. In the quantitative evaluation, multiple regressions were performed with the data obtained through the questionnaire adapted from Chory-Assad (2007) and Simil (2016) studies, in order to evaluate whether the socio-demographic and control variables exerted influence on the perception of students. The qualitative analysis was performed through the analysis of interviews, which were carried out through a semi-structured script with six students who agreed to grant it. Quantitative analyzes indicate that of the nine variables tested, only three variables were statistically significant. They are: the variable gender for procedural justice, the variable shift for procedural and interactional justice, and the variable reprobation for all three dimensions of justice. Subsequently, the qualitative analysis was carried out. The results show that students associate justice in the learning environment, in general, mainly with the teacher figure. In conclusion, therefore, that for the students of Accounting Sciences of the State of Minas Gerais, among the factors analyzed, few influenced their perception of justice. It was possible to perceive that the relationship between teacher and student, and the way he organizes the class schedule, has more influence on students' perception of justice than the variables tested in the proposed models.